PERAN PERKEMBANGAN TEKNOLOGI DIGITAL PADA STRATEGI PEMASARAN DAN JALUR DISTRIBUSI UMKM DI INDONESIA (Studi Kasus: UMKM Kuliner Tanpa Restaurant ‘Kepiting Nyinyir’) - Devi Krisnawati (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
The aim of this study is to describe the interchanging role of digital marketing and traditional marketing as the key marketing strategi and marketing mix of the Small Medium Enterprise in Indonesia. The study using qualitative descriptive methods with case study ‘Kepiting Nyinyir’, one of Small Medium Enterprise in Jakarta. The result of this study found significant role of digital technology supported the distribution channel of Small Medium Enterprise to expand the business. Digital marketing as the new concept and perspective is interchanging the role of traditional marketing by balancing online and offline activities. The interchanging role of digital marketing and traditional marketing showed shifting in marketing strategy, from segmentation and targeting to customer community confirmation, brand positioning & differentiation to brand clarification of character and codification, tactical marketing mix (product, place, price & promotion) to connected marketing mix (co-creation, communal activation, currency & conversation).